An atomic-defect enhanced Raman scattering (DERS) quantum probe for molecular level detection – Breaking the SERS barrier. (September 2019) - Dharmalingam, Priya; Venkatakrishnan, Krishnan; Tan, Bo
Graphical abstract: Highlights: Introduced atomic-scale defects to functionalize non-plasmonic quantum sized probes. Magnified defect transformed inactive SERS substrate to highly enhanced Raman active probes (TiO2− x ). Quantum probes exhibits wavelength independent and non-degradable activity for broadband long-term application. The probe activity was investigated for ultrasensitive cancer biomolecule detection (10 −9  M). Varying defect percentage was achieved by tuning ionization potential during ultrafast multiphoton ionization. Abstract: Recently, nonplasmonic surface-enhanced Raman scattering (SERS) has gained intense interest. Compared to commonly studied noble metals, semiconductors offer more uniformity, better chemical stabilities and improved biocompatibilities, which are promising for their broader practical applications. Unfortunately, semiconductors suffer from very low enhancement efficiencies and poor sensitivities because the Raman enhancement primarily comes from charge transfer, which is a weaker mechanism compared to the plasmonic resonance of noble metals. Introducing oxygen defects has been proven to be an effective way to significantly improve the Raman activity of metal-oxide semiconductors. However, current techniques are limited to introducing surface defects, and thus the improvement is limited as a result. Herein, we demonstrate atomic-defect enhanced Raman scattering (DERS) as a new addition to the RS family. The high concentration of defects in the surface and subsurface layers of these small quantum probes improves the sensitivity of semiconductor to a detectable molecular concentration of 10 −9  M with a high enhancement factor of ∼10 10 for the target molecule (CV). The enhancement efficiency, which is comparable to that of noble metals, is achieved by the synergistic contributions of the quantum size coupled with the excellent charge-transfer (CT) enabled by the enriched electronic states that result from the high density of defects. The nonplasmonic quantum probe also exhibits outstanding applicability for detecting biomolecules with low Raman cross-sections. In addition, the DERS probe demonstrates wavelength-independent sensing and nondestructive long-term activity, which validate the consistency of the DERS system and its universality for use in various other fields. This defect-rich nonplasmonic quantum sensor is synthesized by an ultrafast laser-induced multiphoton ionization mechanism, and the surface/subsurface defect ratio within the DERS probes can be precisely tuned by varying the laser energy.